The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1073/pnas.1701812114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory engrams in perception and memory

Abstract: Nervous systems use excitatory cell assemblies to encode and represent sensory percepts. Similarly, synaptically connected cell assemblies or "engrams" are thought to represent memories of past experience. Multiple lines of recent evidence indicate that brain systems create and use inhibitory replicas of excitatory representations for important cognitive functions. Such matched "inhibitory engrams" can form through homeostatic potentiation of inhibition onto postsynaptic cells that show increased levels of exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 89 publications
(152 reference statements)
10
126
0
Order By: Relevance
“…3K) their firing rates in association with good memory performance. The finding of both positive and negative memory-sensitive cells is in 130 line with previous human single-neuron recordings (20), and negative memory-sensitive cells may be related to inhibitory engrams (21). We observed that memory-related firing rate changes were common among anchor cells (17 of 58 anchor cells were memory-sensitive cells; chi-squared test, χ²=11.709, P<0.001), but not among direction, place, or other cells (all χ²<1.717, all P>0.190; Fig.…”
Section: Main Textsupporting
confidence: 90%
“…3K) their firing rates in association with good memory performance. The finding of both positive and negative memory-sensitive cells is in 130 line with previous human single-neuron recordings (20), and negative memory-sensitive cells may be related to inhibitory engrams (21). We observed that memory-related firing rate changes were common among anchor cells (17 of 58 anchor cells were memory-sensitive cells; chi-squared test, χ²=11.709, P<0.001), but not among direction, place, or other cells (all χ²<1.717, all P>0.190; Fig.…”
Section: Main Textsupporting
confidence: 90%
“…The reward system integrates across dimensions to generate abstract decision variables; that is, ones that are correlated with value (e.g. Barron et al, 2017; Blanchard et al, 2015; Fellows, 2006; Hayden, 2016; Hunt and Hayden, 2017; Raghuraman and Padoa-Schioppa, 2014; Strait et al, 2014; Suzuki et al, 2017). However, unlike the visual system, which has only one major input locus—the eyes—the reward system has many inputs.…”
Section: Untangling Information In Form Visionmentioning
confidence: 99%
“…Precisely balanced networks, with all input subsets balanced, are well suited for input 612 gating (Barron, Vogels, Behrens, & Ramaswami, 2017;Hennequin et al, 2017). The finding that 613 most CA1 cells can be converted to place cells for any arbitrary location predicts the existence 614 of an input gating mechanism (Lee, Lin, & Lee, 2012), but the nature of this mechanism remains 615 unknown.…”
Section: Precise Balance In the Hippocampus 602mentioning
confidence: 99%